Maritime piracy (UN New YorkUS, 2014)
Provides an overview of the contemporary international legal regime countering piracy and identifies key examples of international cooperation and multilateral initiatives to combat piracy.
Contents: v. 1 : An Overview of trends, costs and trade-related implications. - v. 2 : An Overview of the international legal framework and of multilateral cooperation to combat piracy.